Unusual reaction of [NiFe]-hydrogenases with cyanide. - Hexter, S; Chung, M; Vincent, K; Armstrong, F (American Chemical Society, 2014)
Cyanide reacts rapidly with [NiFe]-hydrogenases (hydrogenase-1 and hydrogenase-2 from Escherichia coli) under mild oxidizing conditions, inhibiting the electrocatalytic oxidation of hydrogen as recorded by protein film electrochemistry. Electrochemical, EPR, and FTIR measurements show that the final enzyme product, formed within a second (even under 100% H2), is the resting state known as Ni-B, which contains a hydroxido-bridged species, Ni(III)-μ(OH)-Fe(II), at the active site. "Cyanide inhibition" is easily reversed because it is simply the reductive activation of Ni-B. This paper brings back into focus an observation originally made in the 1940s that cyanide inhibits microbial H2 oxidation and addresses the interesting mechanism by which cyanide promotes the formation of Ni-B. As a much stronger nucleophile than hydroxide, cyanide binds more rapidly and promotes oxidation of Ni(II) to Ni(III); however, it is quickly replaced by hydroxide which is a far superior bridging ligand.